Co-creation of the green smart city concept. Analysis of the maturity of municipalities in the Polish- German borderland region - Łaźniewska, Ewa; Janicka, Izabela; Gorecki, Tomasz (TeMA - Journal of Land Use, Mobility and Environment, 2021)
This article discusses the results of research conducted in the Polish-German borderland region regarding the ecological maturity of municipalities in 2020. Our main thesis is that the ecological strength of municipalities lies in the diversity of approaches taken towards solving problems related to environmental protection, and in the continuous activation of municipalities in their pursuit of the “green smart city” model, which in turn contributes to raising the standard of living for the residents. The aim of the study is an attempt to assess the activity of municipalities in the Polish-German borderland region via a tool for studying the ecological maturity of municipalities. The following milestones were adopted in the research: surveying municipalities in the Polish-German borderland area in terms of their ecological maturity, conducting a comparative analysis of the survey results, and formulating recommendations for the further development of municipalities and ecological policy.